Kecemasan sosial dan intensitas penggunaan media sosial pada remaja - Permadi, Dimas Agil (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
Social media is a medium that helps humans interact with other humans. People with social anxiety avoid social situations such as appearing in public, interacting with new people and expressing opinions in public. Individuals with social anxiety feel afraid and anxious about other people's negative thoughts on him. This study was conducted to examine the correlation between social anxiety and duration of social media use. The subjects in this study were 88 social media users, the scale was distributed via the Google form. This study shows that there is a positive relationship between social anxiety and the duration of social media use, with the results of the correlation test as follows r=0.609; p=0.000.